Disciplina de didática: um estudo exploratório a partir dos planos de ensino - Franco, Maria Amélia Santoro; Guarnieri, Maria Regina [UNESP] (My University, 2011)
The present investigation intended to understand how Didatic has been interpreted by teachers who work with this discipline in undergraduate courses. We assume that there are still many controversies and contradictions in consideration of the epistemological status of didactics, and that this knowledge object is on constant review by professionals. Initially we were seeking evidence in the plans of courses, however, this search has put us in a situation of confusion, of uncertainty and highlighted structural problems which, at first, prevented us from using pure and simple of the contents of the plans. We analyzed 76 lesson plans, allocated to institutions in different Brazilian states, different types of institutions and the diversity was so great that led us to characterize this study as exploratory and tell us the relevance of analyzing them in the perspective of "facets". To deepen the understanding we were interviewing teachers and two focus groups conducted with teachers of Teaching. Triangulating the analysis of plans, with the reflections from the interviews, the speeches and also in the focus group data, observation of teaching practice, we put some insights on issues, even though preliminary and will require further research.

A presente investigação teve por perspectiva compreender como a Didática tem sido interpretada por professores que atuam com esta disciplina nos cursos de licenciatura. Partimos do pressuposto de que ainda há muitas controvérsias e contradições na consideração do estatuto epistemológico da Didática, e que este objeto de conhecimento encontra-se em constante revisão pelos profissionais da área. Inicialmente fomos buscar indícios nos planos de cursos; no entanto, essa busca nos colocou em uma situação de perplexidade, de indefinição e trouxe à tona problemas mais estruturais que, em um primeiro momento, nos impediu a utilização pura e simples dos conteúdos dos planos. Analisamos 76 planos de ensino, alocados em instituições de diferentes estados brasileiros, de diferentes tipos de instituição. A diversidade foi tão grande que nos levou a caracterizar esse estudo como exploratório e a nos indicar a pertinência de analisá-los na perspectiva de “facetas”. Para aprofundar a compreensão da temática, entrevistamos os professores e realizamos dois grupos focais com docentes de Didática. Triangulando a análise dos planos com as reflexões a partir das entrevistas, das falas no grupo focal e, ainda, dos dados de observação da prática docente, colocamos em questões algumas compreensões, ainda que prévias e que demandarão uma pesquisa mais aprofundada
Keywords: Teacher Education; Didatic; Teaching; Teaching Plans; Formação de Professores; Didática; Planos de Ensino